2016
DOI: 10.1039/c6cp02338j
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of La1−xSrxMnO3perovskite catalysts for hydrogen peroxide reduction

Abstract: We investigated the crystalline phase and electronic structure of perovskite-type La1-xSrxMnO3 (0.0 ≤ x ≤ 1.0) (LSMx) catalysts synthesized via the citric sol-gel route, for H2O2 reduction. The resulting materials were characterized by XRD, XANES, TR-XANES, and TPO and, after calcination, consisted of cubic perovskite for 0.0 ≤ x ≤ 0.8 and hexagonal perovskite for x = 1.0. Mn species in the precalcined catalysts were oxidized to Mn(3+) for x = 0.0 to 0.6 and to Mn(2+) for x = 0.8 and 1.0. After calcination, Mn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 43 publications
0
8
0
Order By: Relevance
“…Accordingly, this method of measuring current in a solution of hydrogen peroxide cannot be used to definitively differentiate between HPER (step 3b in Figure ) and HPCD (step 3c in Figure ). Using this method, a variety of perovskites have been assumed to be active for HPER. ,, Additionally, the combination of chemical and electrochemical steps (HPCD plus subsequent oxygen reduction) has also been assumed by several researchers. ,, Therefore, this method will be described generically as measuring hydrogen peroxide reduction reaction (HPRR) activity. An example of this HPRR activity measurement was also performed by Fabbri et al for BSCF and is shown in Figure .…”
Section: Reaction Mechanismsmentioning
confidence: 99%
“…Accordingly, this method of measuring current in a solution of hydrogen peroxide cannot be used to definitively differentiate between HPER (step 3b in Figure ) and HPCD (step 3c in Figure ). Using this method, a variety of perovskites have been assumed to be active for HPER. ,, Additionally, the combination of chemical and electrochemical steps (HPCD plus subsequent oxygen reduction) has also been assumed by several researchers. ,, Therefore, this method will be described generically as measuring hydrogen peroxide reduction reaction (HPRR) activity. An example of this HPRR activity measurement was also performed by Fabbri et al for BSCF and is shown in Figure .…”
Section: Reaction Mechanismsmentioning
confidence: 99%
“…Yunphuttha et al analysed La 1-x Sr x MnO 3 perovskite catalysts for hydrogen peroxide reduction by La L 1 -edge XANES spectra. [37] Unfortunately, these analyses are mostly qualitative ones without BAA index, but hopefully, there can be a bit sophisticated way to analyse advanced materials as discussed in the next section.…”
Section: Example Of Local Structure Analysis By Ln L 1 and L 3 -Edge mentioning
confidence: 99%
“…As these steps overall conserve the spin, the reduced magnetic entropy in half metals means the electrochemical reaction will be limited by the transference of the electrons with the minority spin (DOWN) if EBand.GapDOWNkBT . As verified, LSMO ( T C >300 K) will suffer this particular limitation; this constitutes the second general design principle related with the magnetic state of the catalyst as conclusion of this work: If H 2 O is the final desired product, essentially PM good conductors such as La 0.4 Sr 0.6 MnO 3 seem optimum for complete ORR …”
Section: Resultsmentioning
confidence: 70%
“…La 1− x Sr X MnO 3 compositions with a half‐metallic ground state (G.S.) have consistently been reported as oxides with a high intrinsic ORR activity . Intermediate oxidation states must be carefully controlled for the stabilisation of the appropriate electronic–magnetic phase for good activity .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation